Análise de aberturas subterrâneas circulares pelo método dos elementos finitos - Pereira, Paulo Roberto (1977)
The present dissertation is about a two-dimensional computer program for the analysis of underground openings under plane-strain conditions. The numerical analyses are carried out by means of Finite Element Method (FEM) the quadratic isoparametric element being used. Linear and bi-linear elastic behaviours are assumed. Soils heterogeneity and sequential excavation are taken into account. The shield construction method for tunneling in soils is simulated in some examples. A structural modelling is assumed for the study of underground excavations through the finite elements. Comparisons of numerical results with existing solutions show that the FEM is reliable.